Perfection of mechanism of estimation and management labour potential in the conditions of adaptation to requirements of international integration - Dobykina, Y. (Економічний вісник Донбасу, 2016)
In this article it is accented that in the crisis of the world economy and, especially for countries with transformational nature of management, of particular relevance is optimal formation of such an element of the economic potential of the enterprise as the labour potential. This urgency is due to the fact that this factor is fundamental as a catalyst of such an intangible asset of the company as goodwill. The approaches of valuation of labour potential are considered. In order to improve the employment potential of the control system an analysis of the labour potential competitive space is proposed, that allows to evaluate systematically all its characteristics. The trajectory in the competitive space for the purpose of company goodwill formation and, finally, for the market value increase is suggested as well